Postural control in individuals with Down syndrome: a review (Fisioterapia e Pesquisa, 2008)
This is a review of literature on postural control in individuals with the Down syndrome, by searching in Medline, Lilacs and Web of Science data bases. Among articles published in the last 16 years, 30 were selected, of which 7 focus on postural control system deficits, such as neurobiological and biomechanical alterations, and 23 focus postural control development (11 articles) and in adolescents and adults (12 articles) with the Down syndrome. The theoretic bases for understanding posture control development and deficits are discussed, in view of their implications for physical therapy practice.